To Study the Efficacy of Ferrum Phos in Management of Iron Deficiency Anemia (Advancements in Homeopathic Research, 2022)
Iron deficiency anemia is a common type of anemia — a condition in which blood lacks adequate healthy red blood cells. Red blood cells carry oxygen to the body’s tissues. As the name implies, iron deficiency anemia is due to insufficient iron. Without enough iron, your body can’t produce enough of a substance in red blood cells that enables them to carry oxygen (hemoglobin). As a result, iron deficiency anemia may leave you tired and short of breath. You can usually correct iron deficiency anemia with iron supplementation. Sometimes additional tests or treatments for iron deficiency anemia are necessary, especially if the doctor suspects that you’re bleeding internally. In the countries like India many people suffer from iron deficiency. It is observed that people from a financially good background are also not spared from the iron deficiency anemia. Homoeopathy has lots to offer in such cases. It not only increases the Hb% but also aids in increasing the iron levels and can be easily consumed along with other iron supplements.
Keywords: Anemia; Iron Deficiency; Haemoglobin; Red Blood Cells